Tales From Grades 1 Through 12: Understanding the Complex Web of Multiple Life Forces Located in Schools - Dieser, Rodney B. (Alberta Journal of Educational Research, 2008)
This study is a qualitative autoethnographical narrative of my grades 1 through 12 experiences in a Catholic school system in Alberta. Autoethnographical research interprets a culture by producing highly personalized and revealing texts; it examines social phenomena holistically and underscores how social histories influence identity development. To this end, this study brings clarity and understanding to the complex web of multiple societal forces in life that are located in schools (e.g., educational policy, hegemonic masculinity and femininity, play and recreation, family history, family health problems, youth identity development, popular culture, care theory, socioeconomic status, extracurricular school clubs) and in making difficult decisions related to improving the ecology of schooling.